Potential for regeneration inhibition of roots and seedlings in germinating Eugenia pyriformis seeds - Amador, Talita Silveira; Barbedo, Claudio José (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate the potential for inhibiting the formation of new roots and seedlings from germinating seeds of "uvaieira" (Eugenia pyriformis), fragmented and fissured. Seeds were separated by size into two groups. Each group was separated into two subgroups, one of which was subjected to germination test. Seeds of each subgroup were subjected to two types of incision (total or partial) and, then, evaluated as for the production of roots and seedlings. Seeds with partial incision, which had only one developed plantlet, had the incision completed until the halves were separated. The half fragment containing the root was discarded, and its complementary part was placed to germinate, in order to evaluate the production of roots and seedlings in these fractions without the roots. The design in all the experiments was completely randomized, in a 2x2 factorial arrangement (length x seed visible germination) or 2x4 (seed size x incision type). Fragmented seeds of "uvaieira" shows potential for root and seedling regeneration and can produce more than one seedling per seed. Germination starts inhibition processes of formation of new roots and plantlets, and the incision of cotyledons can block this inhibition.